Dual Role for FHY3 in Light Input to the Clock - Rhodes, Bruce M.; Siddiqui, Hamad; Khan, Safina; Devlin, Paul F. (Frontiers in Plant Science, 2022)
The red-light regulated transcription factors FHY3 and FAR1 form a key point of light input to the plant circadian clock in positively regulating expression of genes within the central clock. However, the fhy3 mutant shows an additional red light-specific disruption of rhythmicity which is inconsistent with this role. Here we demonstrate that only fhy3 and not far1 mutants show this red specific disruption of rhythmicity. We examined the differences in rhythmic transcriptome in red versus white light and reveal differences in patterns of rhythmicity among the central clock proteins suggestive of a change in emphasis withing the central mechanism of the clock, changes which underlie the red specificity of the fhy3 mutant. In particular, changes in enrichment of promoter elements were consistent with a key role for the HY5 transcription factor, a known integrator of the ratio of red to blue light in regulation of the clock. Examination of differences in the rhythmic transcriptome in the fhy3 mutant in red light which identified specific disruption of the CCA1-regulated ELF3 and LUX central clock genes, while the CCA1 target TBS element, TGGGCC, was enriched among genes that became arrhythmic. Coupled with the known interaction of FHY3 but not FAR1 with CCA1 we propose that the red-specific circadian phenotype of fhy3 may involve disruption of the previously-demonstrated moderation of CCA1 activity by FHY3 rather than a disruption of its own transcriptional regulatory activity. Together, this evidence suggests a conditional redundancy between FHY3 and HY5 in the integration of red and blue light input to the clock in order to enable a plasticity in response to light and optimise plant adaptation. Furthermore, our evidence also suggests changes in CCA1 activity between red and white light transcriptomes. This, together with the documented interaction of HY5 with CCA1, leads us to propose a model whereby this integration of red and blue signals may at least partly occur via direct FHY3 and HY5 interaction with CCA1 leading to moderation of CCA1 activity.